Novel insights from human induced pluripotent stem cells on origins and roles of fibro/adipogenic progenitors as heterotopic ossification precursors - Zhao, Chengzhu; Ikeya, Makoto (Frontiers in Cell and Developmental Biology, 2024)
Fibro/adipogenic progenitors (FAPs) that reside in muscle tissue are crucial for muscular homeostasis and regeneration as they secrete signaling molecules and components of the extracellular matrix. During injury or disease, FAPs differentiate into different cell types and significantly modulate muscular function. Recent advances in lineage tracing and single-cell transcriptomics have proven that FAPs are heterogeneous both in resting and post-injury or disease states. Their heterogeneity may be owing to the varied tissue microenvironments and their diverse developmental origins. Therefore, understanding FAPs’ developmental origins can help predict their characteristics and behaviors under different conditions. FAPs are thought to be the major cell populations in the muscle connective tissue (MCT). During embryogenesis, the MCT directs muscular development throughout the body and serves as a prepattern for muscular morphogenesis. The developmental origins of FAPs as stromal cells in the MCT were studied previously. In adult tissues, FAPs are important precursors for heterotopic ossification, especially in the context of the rare genetic disorder fibrodysplasia ossificans progressiva. A new developmental origin for FAPs have been suggested that differs from conventional developmental perspectives. In this review, we summarize the developmental origins and functions of FAPs as stromal cells of the MCT and present novel insights obtained by using patient-derived induced pluripotent stem cells and mouse models of heterotopic ossification. This review broadens the current understanding of FAPs and suggests potential avenues for further investigation.